2009
DOI: 10.1519/jsc.0b013e3181a3928b
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Physiological Demands of Elite Rugby Union Using Global Positioning System Tracking Software

Abstract: The current case study attempted to document the contemporary demands of elite rugby union. Players (n = 2) were tracked continuously during a competitive team selection game using Global Positioning System (GPS) software. Data revealed that players covered on average 6,953 m during play (83 minutes). Of this distance, 37% (2,800 m) was spent standing and walking, 27% (1,900 m) jogging, 10% (700 m) cruising, 14% (990 m) striding, 5% (320 m) high-intensity running, and 6% (420 m) sprinting. Greater running dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
305
7
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(368 citation statements)
references
References 25 publications
13
305
7
16
Order By: Relevance
“…Research revealed that these strategies increased force produced during the tasks such as bench press, hand grip, weightlifting, leg extension (4,11,31,34,37,40,43), muscular endurance (8), power (42), and sprint (8,10,11,16,19)]. The common belief among many athletes is that the use of these strategies will enable them to lift heavier loads (33).…”
Section: Au9mentioning
confidence: 99%
“…Research revealed that these strategies increased force produced during the tasks such as bench press, hand grip, weightlifting, leg extension (4,11,31,34,37,40,43), muscular endurance (8), power (42), and sprint (8,10,11,16,19)]. The common belief among many athletes is that the use of these strategies will enable them to lift heavier loads (33).…”
Section: Au9mentioning
confidence: 99%
“…[1,2] To ensure the conditioning and recovery programmes of the players are appropriate, it is essential to have a good understanding of the physical demands placed on players in these different positions. [3] A number of researchers have endeavoured to quantify the physical demands of rugby union through video-based time-motion analysis (TMA). [1,2,[4][5][6] These studies all agree that the majority of time is spent engaged in low-intensity activities for all positions, but that the nature of physical exertion differs across position groups.…”
mentioning
confidence: 99%
“…[9] To date, only four studies have been published describing the movement characteristics of elite professional rugby union players. [3,[10][11][12] The first two of these, Cunniffe et al [3] and Coughlan et al, [10] used similar methodology: tracking a single forward and a single back during an international rugby union match. The results were similar: players covered >6 500 m in both studies and the backs performed a greater number of high-intensity runs and reached greater maximal speeds than the forwards did.…”
mentioning
confidence: 99%
“…El PL fue registrado mediante acelerometría (Boyd, Ball, &Aughey, 2011;Casamichana, Castellano, & Castagna, 2012;Cunniffe, Proctor, Baker, & Davies, 2009) usando un acelerómetro triaxial de 100 Hz que combina las aceleraciones producidas en tres planos de movimiento del cuerpo. El PL es un indicador que tiene gran correlación con indicadores como el Edwards y sesión RPE .…”
Section: Variables Físicasunclassified